2017
DOI: 10.3174/ajnr.a5072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Collaterals and Clot Burden Using Time-Resolved C-Arm Conebeam CT Angiography in the Angiography Suite: A Feasibility Study

Abstract: BACKGROUND AND PURPOSE:The assessment of collaterals and clot burden in patients with acute ischemic stroke provides important information about treatment options and clinical outcome. Time-resolved C-arm conebeam CT angiography has the potential to provide accurate and reliable evaluations of collaterals and clot burden in the angiographic suite. Experience with this technique is extremely limited, and feasibility studies are needed to validate this technique. Our purpose was to present such a feasibility stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Concerning question 3 and 4, our study, together with findings from Yang et al (already demonstrating the feasibility of collateral status evaluation with FDCTA [ 23 ]), provides further evidence for the use of FDCTA in the one-stop management paradigm in acute ischemic stroke. We could demonstrate, that this method has equal predictive value compared to DSA derived collateral status evaluation.…”
Section: Discussionsupporting
confidence: 69%
“…Concerning question 3 and 4, our study, together with findings from Yang et al (already demonstrating the feasibility of collateral status evaluation with FDCTA [ 23 ]), provides further evidence for the use of FDCTA in the one-stop management paradigm in acute ischemic stroke. We could demonstrate, that this method has equal predictive value compared to DSA derived collateral status evaluation.…”
Section: Discussionsupporting
confidence: 69%
“…This confirms prior results of other work groups who used it successfully for evaluating collaterals and the clot-burden score. 15,16 Collaterals can be used as an additional tool for patient selection as pointed out by Schregel et al, 17 who compared the prognostic value of CBV-ASPECTS and collaterals. Although the time resolution of the FPDCT perfusion is 5 seconds lower than the time resolution of the MDCT Perfusion (1.5 seconds), motion artifacts were not a serious issue in our small cohort.…”
Section: Discussionmentioning
confidence: 99%
“…New, yet prototype-based, 4D-FDCTA could probably improve the delineation of collateral supply and the description of the clot (28). Yang et al recently reported a comprehensive evaluation of vessel occlusions by using time-resolved FDCTA (29). However, these results are based on not commercially available prototypes, where issues such as C-arm rotational speed, patient safety, and radiation exposure first need to be addressed.…”
Section: Discussionmentioning
confidence: 99%